Social Distancing: Risk or Prevention Factor? Foreword - Francese, Maria Teresa Mara (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2022)
In a hyper-technological society such as ours, characterized by ever-increasing possibilities of constant connections, children, teenagers and young people are exposed to new technologies which they use to express themselves and relate to others. The lack of adequate preparation for the correct use of these tools can put them at risk. Interpersonal relationships can be distorted to such an extent that the virtual dimension often has the same value as the real one or completes it in a complementary way. A direct consequence is the growth, in recent years, of episodes of cyberbullying which have had and continue to have significant repercussions on the well-being of young people.